Critical Factors Influencing the Behavioral Intention of Consumers towards Mobile Banking in Malaysia - Rehman, Z. U.; Shaikh, F. A. (Engineering, Technology & Applied Science Research, 2020)
Mobile banking services are widely adopted in developed and developing countries, while their adoption by Malaysian consumers is relatively low. The effective adoption of mobile banking mostly depends on consumers. This study’s objective was to examine the factors that influence Malaysian customers’ behavioral intention toward mobile banking. A detailed literature review was conducted in order to identify the critical factors that affect mobile banking users. The research model was based on the Technology Acceptance Model, investigating the additionally perceived risk. Primary data were collected from 384 generation Y bank customers. Structure equation modeling through Smart-PLS was used for data analysis. Results revealed that consumers’ behavioral intention was significantly and positively influenced by perceived usefulness and ease of use, while a significant negative relationship was found between consumers’ behavioral intention and perceived risk. The findings also revealed a mediating relationship of attitude between perceived usefulness, ease of use and risk, and behavioral intention to use mobile banking. The study provides appropriate guidelines to Malaysian banks and mobile banking application developers for the effective implementation and design of mobile banking services.